2020
DOI: 10.1002/jcb.29830
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquilin proteins regulate EGFR levels and activity in lung adenocarcinoma cells

Abstract: Ubiquilin (UBQLN) proteins are involved in diverse cellular processes like endoplasmic reticulum‐associated degradation, autophagy, apoptosis, and epithelial‐to‐mesenchymal transition. UBQLNs interact with a variety of substrates, including cell surface receptors, transcription factor regulators, proteasomal machinery proteins, and transmembrane proteins. In addition, previous work from our lab shows that UBQLN1 interacts with insulin‐like growth factor receptor family members (IGF1R, IGF2R, and INSR) and this… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…To further elucidate the biological role of UBQLN1 in breast cancer, the influence of UBQLN1 knockdown on biological behavior in vitro was investigated, in particular regarding metastasis. In contrast to the tumor suppressor role reported in lung cancer cells ( 6 , 11 , 35 ), the present study found that the knockdown of UBQLN1 inhibited cell migration and invasion, EMT, and MMP2 and MMP9 expression in breast cancer cell lines. EMT has been implicated in carcinogenesis, and confers metastatic properties to cancer cells by enhancing mobility and invasion ( 37 ).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…To further elucidate the biological role of UBQLN1 in breast cancer, the influence of UBQLN1 knockdown on biological behavior in vitro was investigated, in particular regarding metastasis. In contrast to the tumor suppressor role reported in lung cancer cells ( 6 , 11 , 35 ), the present study found that the knockdown of UBQLN1 inhibited cell migration and invasion, EMT, and MMP2 and MMP9 expression in breast cancer cell lines. EMT has been implicated in carcinogenesis, and confers metastatic properties to cancer cells by enhancing mobility and invasion ( 37 ).…”
Section: Discussioncontrasting
confidence: 99%
“…UBQLN1 is abnormally expressed in certain cancer types, including lung adenocarcinoma ( 11 , 18 ) and gastric cancer ( 12 ). In the present study, to elucidate UBQLN1 expression in breast cancer, UBQLN1 expression was detected in a tissue array slide, containing samples from 73 breast cancer cases and 30 normal breast tissues by using IHC.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations